2017
DOI: 10.1080/22201181.2017.1397877
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of thrombocytopenia in Caesarean delivery: is routine platelet count testing necessary?

Abstract: Peri-partum thrombocytopenia significantly impacts anaesthetic technique and increases the risk of perioperative bleeding. However, as less than 5% of normal pregnancies have significant thrombocytopenia, routine platelet testing incurs great cost for a relatively low yield. Determining whether clinical predictors, in particular HIV status, are associated with thrombocytopenia may assist clinicians in rationalising preoperative testing. Methods: This was a prospective, observational, single-centre study at a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…Haemoglobin (g/dL) 11 [11][12][13] 12 [11][12][13] 12 [11][12][13] Platelet in the latter period. 8 Our findings were that SA in patients with eclampsia and GCS ≥ 14 appears to be safe and possibly associated with better outcomes for both mother and child.…”
Section: Blood Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemoglobin (g/dL) 11 [11][12][13] 12 [11][12][13] 12 [11][12][13] Platelet in the latter period. 8 Our findings were that SA in patients with eclampsia and GCS ≥ 14 appears to be safe and possibly associated with better outcomes for both mother and child.…”
Section: Blood Resultsmentioning
confidence: 99%
“…10 The incidence of thrombocytopaenia in pregnancy with a platelet count < 75 × 10 9 /L is approximately 1%. 11 A thromboelastography study showed that the maximum amplitude decreased markedly in patients with preeclampsia when the platelet count decreased to below 75 × 10 9 /L. 12 In a recent Pregnancy Practice Bulletin of the American College of Obstetricians and Gynecologists, the recommended lower limit of the platelet count for safe neuraxial anaesthesia is 80 × 10 9 /L.…”
Section: Blood Resultsmentioning
confidence: 99%
“…The authors concluded that on this basis a routine full blood count is indicated in preeclampsia, but not in patients who are HIV-positive, unless there are other comorbidities. 24 Davies et al evaluated differences in healthy pregnant versus preeclamptic women using the Platelet Function Analyzer (PFA-100) and TEG. This study found a mean MA of 73 mm, and that despite an abnormal clotting time in the preeclampsia cohort, the MA remained within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…In an otherwise healthy parturient, HIV infection is not an indication for an FBC, as this does not confer increased risk of moderate thrombocytopaenia in the obstetric population. 10 …”
Section: Are Preoperative Blood Tests Are Required For Spinal Anaesth...mentioning
confidence: 99%
“…In an otherwise healthy parturient, HIV infection is not an indication for an FBC, as this does not confer increased risk of moderate thrombocytopaenia in the obstetric population. 10 Whilst patients with severe preeclampsia should be referred to regional hospitals, many patients with mild preeclampsia are managed at district-level hospitals, and occasionally will progress to severe disease requiring urgent management at district hospitals. The National Guidelines for Hypertension in Pregnancy should be followed.…”
Section: Are Preoperative Blood Tests Are Required For Spinal Anaesth...mentioning
confidence: 99%